Business Plan- Tianlun Village(The retirement village) - LIU, YING (2014)
Tianlun Senior Community Management Ltd is offer 49% of total equity for 25,474,800 RMB. And this is the amount of additional funding that we need to develop our unique retirement village in China that will generate net profits of 5,208,450 RMB a year with the Annualized rate of return of 11.5% by 2020. Finally, we propose approaches for the external fund to get the expected return and safely quit the project. This Business Plan sets out our strategic, operating and financial plan for the next six years and the detailed focus for the next 24 months.